The influence of MgO on the crystallization behaviour and properties of SrO-rich phosphosilicate glasses. Issue 8 (1st June 2020) - Abo-Mosallam, H.A.; Mahdy, Ebrahim A.
Abstract: A series of glass was produced to investigate the effect of MgO/SrO replacement on the crystallization characteristics and properties of phosphosilicate glasses containing high SrO content. The glass samples were synthesized by conventional melting technique based on 5CaO-(40-X)SrO-X MgO– 43SiO2 –7P2 O5 –5CaF2 (where; X = 10, 20, 30 and 40 mol%). The influence of MgO/SrO replacement on phase assemblages, microcrystalline structures, thermal expansion, and mechanical properties was examined as a function of basic chemical compositions and crystallization parameters. Predominant strontium meta-silicates together with strontium fluoroapatite phases are crystallized from the base glass free of magnesium. The substitution of strontium by magnesium up to 50% led to formation strontium akermanite phase Sr2 MgSi2 O7 at the expense of SrSiO3 phase. Whereas the increase of the MgO/SrO of more than 50%, which led to the crystallization of the clino-enstatite MgSiO3 as a predominant phase. The results show that the α-values of the glass-ceramics are ranged in 94–125 × 10 −6 K −1 over the temperature range (25–500 °C). On the other hand, MgO/SrO replacements led to enhancing the microhardness of the resultant crystalline materials from 4713 Mpa to 6744 Mpa. As a result of the designed glass compositions, promising crystalline phases were obtained as well as good thermal and mechanical properties for the resultant glass-ceramics. Therefore, the designed glass-ceramics can be strongly used as biomaterials especially for bone reconstruction applications.